Biological controls for aflatoxin reduction - Bandyopadhyay, Ranajit; Cotty, Peter J. (International Food Policy Research Institute, 2013)
Aflatoxin exposure is frequent and widespread in most African countries where the key staples, maize and groundnut, are particularly vulnerable to aflatoxin contamination. Aflatoxin-producing fungi are ubiquitous in Africa where they occupy soil and colonize diverse organic matter while producing spores that associate with crops leading to aflatoxin formation. Aflatoxins need to be managed throughout this region. A biological control technique that greatly reduces aflatoxin contamination of susceptible crops has been developed by USDA-ARS and is used commercially in the U.S. Over the past decade, USDA-ARS with the International Institute of Tropical Agriculture, has sought to adapt the biological control technology for use in Africa. This effort has resulted in several highly effective aflatoxin management products specifically targeted to regions in need in countries across sub-Saharan Africa. The first generation African biological control products are currently in evaluation trials in farmer’s fields in East, West and Southern Africa environments. Aspergillus flavus occurs in nature in complex communities composed of both aflatoxin-producers and isolates that do not produce aflatoxins (atoxigenic strains). Application of carefully selected atoxigenic strains at appropriate stages in crop development shifts the community composition within the production area from one dominated by aflatoxin producers to one in which beneficial atoxigenic strains dominate. This results in decreased crop aflatoxin contamination. Changes in the A. flavus community structures induced by atoxigenic strain applications occur without increases to the overall amount of A. flavus in the environment and without increases in the amount of the crop infected. Prior to large-scale use in a target country, biocontrol products must be registered with that country’s national biopesticide regulatory agency through a complex process. Registration is based on efficacy, safety, quality and social/economic value of a product. Due to high potential of the technology to reduce aflatoxins, further efforts are required for widespread adoption of biocontrol by creating a flexible and enabling system for biopesticide regulation in tandem with other policy and institutional support. Currently there are atoxigenic strain biocontrol products under farmer’s field evaluations in several African countries extending from West Africa to East and Southern Africa. These products need to be moved into wide use to reduce aflatoxin exposure to the human populations across Africa.